Synthesis and Photophysical Studies of Dansyl Dyads Containing Anthraquinone and Coumarin Moiety - Kaur, Princedeep (My University, 2019)
Anthraquinone and coumarin based dyads with dansyl chloride were synthesized for the detection of CN- ions. Probe 1 showed absorption and emission band at 390 nm and 510 nm in CH3CN : H20 (95 : 5 , v/v) respectively. The addition of CN- ions led to red shift of 63 nm in absorption spectra hence, shifted the band from 387 nm to 486 nm. Similarly, there was a red shift of 100 nm in emission which led to appearance of band at 610 nm from 510 nm accompanied by a visible color change from colorless to dark yellow and fluorescence changed from green to red. The mechanism responsible for the change was cleavage of S-O bond on encounter of CN- ions. The detection limit estimated was 3.5 nM. Probe 2 showed the emission band at 520 nm in CH3CN : H2O (90 : 10, v/v). The addition of CN- ions resulted in an enhancement and a blue shift of 70 nm, thus shifted the band from 520 nm to 450 nm. The fluorescence changed from green to blue.The reason being cleaveage of S-O bond. The detection limit was calculated as 17 nM. Probe 3 showed absorption band at 330 nm and emission was at 466 nm. Probe 3 did not show change with any anion in CH3CN : H2O (90 : 10, v/v).
Keywords: anthraquinone; coumarin; dansyl dyad; chemodositmeter